Battery pack technological considerations for hybrid-electric regional aircraft feasibility - Spinelli, Andrea; Krupa, Gustavo P.; Kipouros, Timoleon; Laskaridis, Panagiotis; Berseneff, Boris (Cambridge University Press (CUP), 2025)
This paper presents a study of the effects of the durability and level of energy storage technology on energy management strategies and the performance of hybrid electric turboprops. The results highlight the key role of battery energy density on the durability of the battery pack and the viability of the concept of hybrid electric aircraft. Additionally, the trade-off between zero-day environmental compatibility and battery lifetime is identified, caused by the size of the pack. The effective energy density would decrease with the aging of the cells, leaving a significant inert mass and increasing fuel consumption. Optimal energy management strategies are suggested in light of this new information. Higher specific energy of the pack would mitigate this aspect, along with a reduction in fuel consumption and NOx emissions. Indeed, the improvement of environmental compatibility was found to be nonlinear with a positive rate, suggesting high returns in investing in great improvements in energy density over a gradual increase. This result relates to the results of the statistical technological forecast presented in this study, which, without an increase in funding, predicts the availability of the specific energy required to match the fuel-only baseline in the 2040–2050 decade.
Keywords: hybrid-electric aircraft; sustainable aviation; aircraft design; battery technology; energy management system; 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy; Aerospace & Aeronautics; 35 Commerce, management, tourism and services